Austroectobius invunche: new genus and species of Ectobiidae for Chile (Insecta, Blattaria) - Vera, Alejandro; Schapheer, Constanza (Zootaxa, 2018)
We describe a new genus and species of Chilean Blattodea (Ectobiidae), collected on Isla Grande de Chiloé and associated with Fascicularia bicolor (Bromeliaceae). We study the morphology of both sexes with SEM. The new taxon is brachypterous, with tiny ellipsoid tegmina and hind wings absent. The female presents strongly sclerotized genital sclerites and spermathecal plate developed. The male without tergal specializationsand asymmetrical styles. Medium phallomere with modified sclerites, compose a sclerotized complex that includes a long ejaculatory duct.